2015
DOI: 10.1001/jamaoncol.2015.3018
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Magnetic Resonance Imaging for Breast Cancer

Abstract: Preoperative breast MRI use has increased substantially in routine clinical practice and is associated with a significant increase in ancillary investigations, wait time to surgery, mastectomies, and contralateral prophylactic mastectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…27 These results are similar to those from earlier retrospective studies from the USA. [24][25][26] Furthermore, a meta-analysis of the effect of MRI on the surgical management of ductal carcinoma in situ did not demonstrate any improvement in surgical outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…27 These results are similar to those from earlier retrospective studies from the USA. [24][25][26] Furthermore, a meta-analysis of the effect of MRI on the surgical management of ductal carcinoma in situ did not demonstrate any improvement in surgical outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, adding breast MRI to the staging work-up may increase cost and patient anxiety and cause undue delays in definitive treatment. [24][25][26][27] While the standard policy is to complete a breast MRI examination and/or MRI-guided breast biopsy within 5 working days in pre-treatment evaluation at our institution, there have been reports in the literature that pre-operative breast MRI led to 22-30-day delays to surgery. 24,27 The objective of this study was to compare DCE MRI with BWBUS for the incremental detection of breast cancer beyond mammography in patients with biopsy-proven primary breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…24 Breslin et al 12 reported a higher number of traditional and advanced imaging tests among women with preoperative MRI, which increased over time (2005–2008). In their large study population (N=52,202) of commercially-insured younger women (<65 years), they concluded that advanced imaging was additive rather than replacing traditional imaging in the diagnostic workup of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, breast mri must be used with discernment given its limited specificity: very low in the earliest reports, but now generally accepted to be in the 60%-80% range [4][5][6][7][8][9][10][11] . Moreover, evidence is increasing that preoperative staging mri might be detrimental to patients, unnecessarily lengthening their investigation time because of the detection of additional nonspecific findings 13,14 and increasing the mastectomy rate with little reduction in re-excision and negative margins rates 15 . In that context, there has been a call for moderation with respect to routine orders for staging breast mri because no randomized controlled trial has yet demonstrated improved survival for women who undergo breast mri 16 .…”
Section: Introductionmentioning
confidence: 99%